Judicial Recognition of Siri Polygamous Marriages for the Welfare of Children: An Analysis of Supreme Court Ruling Number 223 K/AG/2020 - Rahima Safitri (al-Afkar, Journal For Islamic Studies, 2026)
The practice of unregistered polygamous marriage in Indonesia remains a fairly common social phenomenon, despite lacking official recognition by the state. The absence of formal marriage registration often gives rise to complex legal problems, particularly concerning the legal status of children born from such unions. Children born of siri polygamous marriages risk losing fundamental rights, such as inheritance rights, a clear legal identity, and state protection, because their parents’ marriage does not comply with applicable regulations. This study analyzes Supreme Court Ruling Number 233 K/AG/2020, in which the Supreme Court granted a petition to recognize a siri polygamous marriage on the primary ground of protecting the interests of the child, even though this clearly conflicts with Supreme Court Circular (SEMA) Number 3 of 2018. The research employs a normative-legal approach reinforced by two theoretical frameworks: Jasser Auda’s maqasid al-shari‘ah and the theory of restorative justice. The findings show that the ruling represents a form of progressive legal reasoning. The judge placed the protection of progeny (hifzh al-nasl) at the highest point in the hierarchy of maqasid, above formal procedural requirements. The study demonstrates that this judicial recognition of a siri polygamous marriage can be justified under both shari‘ah and Indonesian positive law, provided it is undertaken solely for the best interests of the child. These findings make an important contribution to the development of family law in Indonesia and underscore that protection of children’s rights must be the foremost priority in any legal consideration concerning their parents’ marital status.